Alfabetização e letramento de crianças cegas em diferentes contextos - Kátia Regina da Silva (2018)
This research aimed to investigate the the blind childs beginning reading-writing instruction and literacy processes in a visual cultural context to know and understand the constructed significances about the events and practices of literacy experienced by two children with congenital blindness in their sociocultural contexts. The field research, fulfilled in Belo Horizonte in the year of 2015, included among the participants the mentioned children, their families, the common classes teachers and the Specialized Educational Assistance. The theoretic-methodological foundations allied theoretical contributions of the Ethnographic perspective (GREEN; BLOOME, 1982; GREEN; DIXON; ZAHARLICK, 2005); of New Literacy Studies (GEE, 1991; STREET, 1984, 2014; BARTON, HAMILTON, 1998); and the Social Model of Disability (DINIZ, 2007). The ethnographic approach and its instruments maked the generation of data possible through participant observation, semi-structured interviews and informal conversations to understand how children participate, construct and reconstruct literate practices in their daily lives. From the ethnographic data confronted with the theoretical assumptions, I conclude that the children take possession of literate practices based on their coexistence with literacy practices in their family and school contexts. Participation in interactive situations mediated by writing constituted important experiences for the learning of literate practices by these children. The various literacy events enabled them to construct references about the writings function, even without the mastery of Braille writing or assistive technologies. By participating in situations of writings use they share knowledge of literate culture, even if they face adversities resulting from a visuocentric sociocultural context, which excludes or prevents the full insertion of blind people. From the perspective of literacy as a social practice, the conception that blind children do not have access to written culture until they enter school and learn Braille is deconstructed. Because they are immersed in the written culture, with adequate support - focused on their skills and not on their difficulties - by participating in literacy events and practices in their socio-cultural contexts they can develop increasing autonomy.